Reconstructing the Narrative of Eve’s Creation in Qur’anic Exegesis through Gender and Sufi Perspectives - Husna, Raudhatul; Istiqamah (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
Amid the intensifying global discourse on gender justice, Qur’anic interpretation continues to be shaped by a long-standing legacy of patriarchal exegesis, particularly in narratives concerning the creation of woman. This tension is especially evident in interpretations of Surah al-Nisāʾ verse 1, a passage that affirms humanity’s origin from a single ontological source (nafs wāḥidah), yet has frequently been read through hierarchical frameworks that position women as derivative and subordinate. This article seeks to reconstruct the narrative of Eve’s creation in Qur’anic exegesis by integrating gender analysis with Sufi perspectives as an alternative hermeneutical framework. Employing a qualitative library-based approach, the study draws on classical and contemporary Qur’anic commentaries as primary sources, supported by scholarly literature on gender, Qur’anic hermeneutics, and Islamic ontology. Data were analyzed using critical hermeneutics and thematic analysis to identify ontological assumptions and gender bias embedded in exegetical traditions. The findings demonstrate that hierarchical portrayals of Eve’s creation do not originate from the Qur’anic text itself but from historically contingent patriarchal epistemologies that shaped classical interpretation. Contemporary egalitarian tafsīr emphasizes the shared ontological origin of men and women, while Sufi interpretations further reinforce this equality through concepts of spiritual parity and human perfection (insān kāmil). By integrating these approaches, this study proposes a reconstructive, non-hierarchical model of Qur’anic interpretation that is ethically grounded and contextually responsive. This research contributes to Qur’anic studies by advancing a gender-just and spiritually informed exegesis that remains faithful to the Qur’an’s moral vision while addressing contemporary demands for gender justice.